A consideration of CYP2D6 genetic variations in the Ghanaian population as a potential 'culprit' for the tramadol 'abuse crisis' - Nicholas Ekow Thomford; Susanna Aba Abraham; Samuel Badu Nyarko; Robert Peter Biney (BMC, 2024)
Abstract Background Cytochrome P450 2D6 is involved in the metabolism of several important medicines including opioids. Variations in CYP2D6 have been implicated in drug response and according to the Clinical Pharmacogenetics Implementation Consortium Guideline (CPIC) for CYP2D6, dosing for CYP2D6 substrates should be based on variants carried by individuals. Although CYP2D6 variations in Ghana had been previously recorded, not all variants have been reported in the Ghanaian population. In this exploratory study we set to investigate certain unreported variations in the Ghanaian population in addition to the previously reported ones and use that to understand the tramadol 'abuse' crisis that is currently being experienced in Ghana. Methods This study employed a convenience sampling approach to include 106 unrelated participants who were recruited as part of the PHARMABIOME project. We successfully genotyped 106 samples using Iplex GOLD SNP genotyping protocol after extracting DNA from these individuals. Allele and diplotype frequencies were undertaken by counting from observed genotypes. Comparison of alleles reported from various studies were done. Results Unreported alleles such as *3, *9 and *41 which are classified as no function and decreased function were observed in our study cohort. In addition, variants such as (*1, *2, *4, *5, *10, *17 and *29 were observed with different frequencies. Our study showed 26% representation of intermediate metabolizers (IM) and 2% poor metabolizers (PM) in the study population. Conclusion The implications for informal sector workers who use tramadol for recreational purposes, is that IMs and PMs will overdose as they may have reduced analgesic effects which will translate into increased risks of unforeseen adverse events. We therefore propose that CYP2D6 should be considered in opioid dosage while making use of these observed variations to implement new approaches to tackle the tramadol 'abuse crisis' in Ghana.